THE INFLUENCE OF BRAND IMAGE, CELEBRITY ENDORSER, AND ONLINE CUSTOMER REVIEW ON PURCHASING DECISION ON SKINTIFIC BEAUTY PRODUCTS WITH THE FEAR OF MISSING OUT (FOMO) AS A MEDIATING ROLE - Viecensa Tania Tithes Kinasih; Barkah Barkah; Nur Afifah; Ahmad Shalahuddin; Hasanudin Hasanudin (Jurnal Ekonomi, 2023)
Today's digitally connected world, consumers often experience the Fear of Missing Out (FoMO), which triggers their desire to keep up with the latest trends and products. Skintific is an influential product in the beauty industry, utilising various marketing strategies such as brand image, celebrity endorsers, and online customer reviews to attract and retain customers. This research study examines the influence of brand image, celebrity endorsers, online customer reviews, Fear of Missing Out (FoMO), and their impact on purchasing decisions related to Skintific Beauty Products. To collect data for this study, a sample strategy and a questionnaire distribution approach were employed, namely purposive sampling. The study's sample consisted of 223 respondents who were Skintific product consumers from different parts of Indonesia. To examine the relationship between independent and dependent variables, data were examined using the Structural Equation Model (SEM) AMOS 24. This study shows that brand image, celebrity endorser, and online customer review significantly and positively affect purchasing decision. The study also shows that Fear of Missing Out (FoMO) plays a role in mediating the influence of brand image, celebrity endorser, and online customer review to make purchasing decision. This research is expected to contribute to providing valuable direction for companies and marketers in developing strategies that are more effective and responsive to consumer needs in today's digital era.